2020
DOI: 10.1016/j.rmcr.2020.101295
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive organizing pneumonia associated with COVID-19

Abstract: We report a case of clinically diagnosed secondary organizing pneumonia (SOP) associated with coronavirus disease 2019 (COVID-19). A 70-year-old woman who had been diagnosed with COVID-19 was admitted to Hokkaido University Hospital. Although her fever, cough, dyspnea, and serum C-reactive protein levels improved, she developed rapidly progressive respiratory failure and computed tomography revealed the development of bilateral lung consolidation. Her dyspnea was relieved, and her oxygenation levels and radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
(9 reference statements)
0
18
0
3
Order By: Relevance
“… Treatment: Both patients received antiviral therapy. [Both survived] Horii et al 83 November 2020, Japan (70, Female) Radiological: Admission chest CT showed bilateral GGOs superimposed with interlobular reticulations and crazy-paving pattern that worsen on day 10 but improved on day 17. Treatment: Favipiravir, ciclesonide, nafamostat for 5-7 days but no improvement so oral prednisolone on day 13 with tapering regimen over 3 months.…”
Section: Methodsmentioning
confidence: 99%
“… Treatment: Both patients received antiviral therapy. [Both survived] Horii et al 83 November 2020, Japan (70, Female) Radiological: Admission chest CT showed bilateral GGOs superimposed with interlobular reticulations and crazy-paving pattern that worsen on day 10 but improved on day 17. Treatment: Favipiravir, ciclesonide, nafamostat for 5-7 days but no improvement so oral prednisolone on day 13 with tapering regimen over 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…1 study was found by manually searching ( Zeng et al, 2020 ).Of these, 1 meeting abstract, 2 not written in the English language, 40 not relevant, 2 reviews were excluded. The full text of 33 remained studies was assessed for eligibility and 12 case reports or case series ( Horii et al, 2020 ; Inoue et al, 2020 ; Ito et al, 2020 ; Nakamura et al, 2020 ; Scarpati, 2020 , Shibata et al, 2020 ; Shimazu et al, 2020 ; Zeng et al, 2020a ; Fukada et al, 2021 ; Sumimoto et al, 2021 ; Suzuki et al, 2021 ; Yamaya et al, 2021 ), 2 studies that did not report the results clearly ( Miyagami et al, 2021 ; Takeshita et al, 2021 ), 3 studies that did not classify patients based on disease severity ( Frix et al, 2020 ; Chen et al, 2021a ; Scotto et al, 2021 ) and 1 preprint study ( Alimova et al, 2020 ) were excluded. Finally, 15 studies identified as relevant and entered the quality assessment ( Awano et al, 2020 , d'Alessandro et al, 2020a , d'Alessandro and Cameli, 2020 , d'Alessandro et al, 2020b ; Frix et al, 2020 ; jp, 2020 , Saito et al, 2020 ; Wang et al, 2020 ; Xue et al, 2020 ; Anai et al, 2021 ; Bergantini et al, 2021 ; Chen et al, 2021 , d’Alessandro et al, 2021 ; Deng et al, 2021 ; He et al, 2021 ; Peng et al, 2021 ; Scotto et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although most contraindications are relative under normal circumstances, patients with a young age or failure of no more than one organ should be given priority for ECMO during a pandemic, when supplies and equipment are limited [ 27 ]. ECMO should be considered for SARS-CoV-2-induced SOP in the late phase of infection, since OP-related respiratory failure is usually reversible [ 28 , 29 ]. The introduction of V-V ECMO in patients with COVID-19-related SOP should be further studied, because systemic corticosteroid treatment might fail, as seen in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Yamagishi et al showed that OP with high serum concentrations of SP-D relapsed more frequently than with low SP-D concentrations [ 27 ]. A recent case report by Horii et al identified KL-6 and SP-D as possible biomarkers to evaluate SOP during COVID-19 treatment [ 28 ]. On the other hand, several prognostic biomarkers, including SP-D, have been identified among patients with COVID-19 [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%